Ascorbic acid and ground beef display life - Shivas, S.D.; Kropf, Donald H.; Hunt, Melvin C.; Kendell, J.L.A.; Dayton, A.D.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station, 2010)
Adding .05 and .10% ascorbic acid to ground beef resulted in brighter color and longer display life, more intense taste panel beef flavor and less rancidity. Those advantages should encourage centralized retail cutting and packaging by reducing spoilage and loss. Ground beef with 25% fat had brighter color scores and lower microbial counts but was more off-flavor than 20% fat ground beef.
Keywords: Beef; Ascorbic acid; Ground beef